Aplicaciones de regla de tres simple - Trebejo Chicchis, Kempes Dionicio (2018)
This professional sufficiency work is titled "Three Simple Rule Applications" taking as mathematical competence Solves quantity problems, which is designed for the first secondary education grade. The introduction generally covers the methodological guide on which the area of mathematics for this cycle is based. In Chapter I is the learning session that has the purpose, competencies and capabilities ending performances. The evaluation I am mentioning will be formative according to the subject presented, in addition to the three moments that a session must have. Thus closing with the bibliography for the teacher and student. In the second chapter it is dedicated to the theoretical and pedagogical sustentum in which we will mention the pedagogical, didactic processes, as well as take some pedagogical currents such as the cognitivista "learning is produced from experience" and end with the evaluation instrument